Analisis Dampak Inflasi dan Investasi Syariah Pada Pertumbuhan Ekonomi Indonesia - Amelia, Amelia (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this research journal is to analyze the impact of inflation and sharia investment on Indonesia’s economic groth. The methodology in only based on written works, including results from published and unpublished research journals with the hope that research journal makers have much broader knowledge of the object of the problem being studied observed. So based on several sources of data obtained, the results of this research journal state that a good level of economic growth is considered as one proof of the success of development in various countries including Indonesia. Considering that Indonesia is a developing country that experiences unstable economic symptoms such as inflation and investment in the Islamic capital market which can have an impact on economic growth. Where there is a relationship between the inflation value factor and the level of investment in the Islamic capital market, which means that inflation has a negative effect on price increases in investment in the Islamic capital market and also on economic growth.